Harassment, Coping Responses, Self-Objectification and Psychological Distress in Female Students Using Public Transport - Sana Zaheer (Corresponding Author); Dr. Humaira Naz (Al-Mahdi Research Journal (MRJ), 2024)
Harassment is a social problem and has been an issue for women using public transport. Current research finds the relationship between harassment, coping responses, self-objectification and psychological distress in women used public transport. A purposive sample of 200 women only who use public transport was chosen in the present research from private and public institutes. Experience of harassment scale, Carver’s brief cope, objectified body consciousness scale and depression anxiety stress scale were employed in this research. Descriptive research method was employed; more specifically, correlational research design. In order to calculate, Pearson Product Moment Correlational coefficient, Stepwise Regression Analysis with backward method was used. The findings showed positive correlation between harassment and psychological distress. The results of regression analysis further showed that among the positive predictors of depression for female adults, the coping strategies like problem-focused coping, active avoidance coping, and body shame were significant. Thus, the physical harassment and body shame configured as the positive predictors of the anxiety level. And stress was found to be knowledgeable by verbal passive harassment, active avoidance coping, and body shame. For the women, the counseling has to be worked out for them in order to implicate the results that indicate distress of harassment. Essentially, safety in public transport should be implemented to prevent the acts of harassment against women.